Learn a Second Language First. A Guide for L2 Research in the Context of Languages Other than English. - Figueiredo, Sandra (2018)
The beliefs of native teachers are strongly based on the monolingual teaching approach that skews the multicultural and variability of skills perspective in the teaching of non-native students.The beliefs of non native students are “monolingual” (sometimes “bilingual”) because they are selfregulated in their only cognitive reference: the home language and culture which generates the learning bias. This learning bias is mostly cognitive and psychosocial and moreover the immigrant students are not fully supported in their new learning and testing. In the context of English as a second language (L2), the implications of the monolingual approach have been studied, but not significantly in second languages other than English. On the one hand, evidence from international studies indicates that less experienced or recently graduated teachers are less oriented towards a bilingual approach, as opposed to more experienced teachers. On the other hand, the second language learners are all different about learning experience: the new generations of immigrant students has prior schooling and culture references that might explain how responding could be these students in a host country. Based on previous studies in Second Language Acquisition (SLA), this book examines the recent literature and trends of research on the expected cognitive processing difference according to the mother tongues of children and their cognitive map structures. Then, it examines the differences according to nationality, focusing on the conditions of the current refugee immigration. This will be followed by a descriptive analysis based on three cases of schools and teachers of the East Coast of the US. Finally, the book argues on the limitations of Common European Framework of Reference for Languages (CEFR, 2001) and, consequently, of the teachers’ practice. Students are expected to present an order of performance according to their proficiency levels (assigned by the schools where they were tested). Our research evidence proves a contradictory scenario.This book is essentially evidence-based and it highlights the risk of underrepresented minorities being misled in host schools in Europe.